Comparison of Five Legumes as Host of Tetranychus sp. (Acari: Tetranychidae) Mass Rearing - Puspitarini, Retno Dyah; Qomariyah, Nurul; Afandhi, Aminudin (AGRIVITA, Journal of Agricultural Science, 2011)
Two spotted mite (TSM) Tetranychus sp. is often used as host for predator mite Phytoseiidae mass rearing. To obtain high population of TSM in short time, it must be reared in host plants that support optimum growth and development. The objective of this research was to observe population development of TSM on legumes such as mungbean (Vigna angularis), adzukibean (V. radiata), snapbean (Phaseolus vulgaris) and soybean (Glycine max) (wilis and anjasmoro cultivars) and to compare the growth of the legumes based on their fresh leaf weight and leaf area, and cost seed index (CSI). The results showed that mungbean was suitable host plant for TSM mass rearing because its population on this legume was the highest. Mungbeanâs fresh leaf weight and leaf area was the highest. If TSM is reared in plant in greenhouse, CSI will become one of criteria for determining the host plant. Although CSI of mungbean was low because TSM population that was reared on it is the highest, the mungbean was the most suitable host plant for TSM growth and development. Another host plant that was suitable for TSM reared was adzukibean.Keywords: legumes, mass rearing, Tetranychus uritcae